Degradation of Acid Violet 7 and Reactive Black 5 in Water by Electro-Fenton and Photo Electro-Fenton by - Ureta-Zanartu, M; Salazar-Gonzalez, R (Sociedad Chilena de Quimica, 2012)
The mineralization of solutions containing azo dyes Acid Violet 7 (AV7) and Reactive Black 5 (RB5) in aqueous solutions using electro-Fenton (EF) and Photo electro-Fenton (PEF) methods were determined. The electrochemical system includes a glassy carbon mesh electrode (cathode) with a concentric outer steel mesh as anode. The optimized parameters were: 0.01 mM of Fe2+ ions, and 250 mA of applied current at pH 3. All experiments were made at 35°C. The degradation was evaluated by color removal and total organic carbon (TOC) decay for solutions of 250 mg L-1 of both cases. The results indicate that the system achieves a degradation efficiency for both dyes proposed, being observed a quickly decolorization of the solutions and the complete transformation of organic compounds to carbon dioxide. The efficiency process and decoloration kinetic constant were evaluated. Generated carboxylic acids such oxalic, oxamic, citric and maleic were found by ion exclusion chromatography. A comparison of the electrochemical system with respect to Fenton s and Photo-Fenton reaction was also performed.